APPLICATION OF THE CAPITAL GAINS AND LOSSES CONCEPT IN PRACTICE. - Arnett, Harold E. (The Accounting Review, 1965)
The principal differences among the bewildering number of concepts of income that may be conceived can be narrowed down to three major issues. These are the real versus the money measure, inclusion versus exclusion of capital gains, and accrual versus realization as the criterion for timing of a gain or loss. If decisions were reached on these three major issues, almost every one of the many controversial points concerning the measurement of income could be settled. And the concept broadened perceptibly up to the present time. It now is identical with the concept "special items" and includes gains and losses presently termed unexpected, unearned, non-recurring, extraordinary, minor or ancillary, non-controllable, as well as those resulting from prior period adjustments or corrections, or are related to capital, as opposed to circulating, assets. Such items, under present generally accepted accounting principles, are supposedly closed directly to retained earnings or reported in a separate section of the income statement, depending upon the materiality of the item in question.